2022
DOI: 10.1038/s41586-022-05223-w
|View full text |Cite
|
Sign up to set email alerts
|

Living material assembly of bacteriogenic protocells

Abstract: Advancing the spontaneous bottom-up construction of arti cial cells with high organisational complexity and diverse functionality remains an unresolved issue at the interface between living and non-living matter. To address this challenge, a living material assembly process based on the capture and on-site processing of spatially segregated bacterial colonies within individual coacervate micro-droplets is developed for the endogenous construction of membrane-bounded, molecularly crowded, compositionally, struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 47 publications
0
94
0
Order By: Relevance
“…Other studies have assembled arrays of negatively charged hydrophilic liposomes, ca. 180 nm in size, on the surface of positively charged coacervate droplets to produce model protocells with multicompartmentalized organization (Figure c). Finally, in very recent work, we used living bacteria as building blocks for the membranization of PDDA/ATP coacervate microdroplets . In this system, populations of negatively charged Pseudomonas aeruginosa bacteria with diameters of 1–2 μm are trapped specifically at the coacervate/water interface to produce a living cell/coacervate hybrid architecture (Figure e,f).…”
Section: Membranized Coacervate Microdroplets Via Interfacial Self-as...mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have assembled arrays of negatively charged hydrophilic liposomes, ca. 180 nm in size, on the surface of positively charged coacervate droplets to produce model protocells with multicompartmentalized organization (Figure c). Finally, in very recent work, we used living bacteria as building blocks for the membranization of PDDA/ATP coacervate microdroplets . In this system, populations of negatively charged Pseudomonas aeruginosa bacteria with diameters of 1–2 μm are trapped specifically at the coacervate/water interface to produce a living cell/coacervate hybrid architecture (Figure e,f).…”
Section: Membranized Coacervate Microdroplets Via Interfacial Self-as...mentioning
confidence: 99%
“…(f) 2D CLSM (bottom) and 3D reconstruction (top) images of bacteria-coated PDDA/ATP coacervate microdroplets ( P. aeruginosa , green fluorescence; coacervate, red fluorescence). Reproduced with permission from ref ( 39 ). Copyright 2022 Springer Nature.…”
Section: Membranized Coacervate Microdroplets Via Interfacial Self-as...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that complex coacervates show no signs of Ostwald ripening, possibly because of the complexed nature of their contents 6 . Peptides, proteins, lipids, and even small molecules can also adsorb at the surface of some coacervates and effectively stabilize them 13 , 14 . And spreading of coacervates at an air-water interface could lead to droplet splitting, thereby providing a way to proliferation 8 .…”
Section: Open Questions On Liquid–liquid Phase Separation For the Ori...mentioning
confidence: 99%
“…Indeed, coacervate droplets (both with and without outer membranes) have been studied by various groups with recent successes in elucidating RNA localization as well as duplex thermodynamics and mechanisms, along with incorporation of bacterial systems for dynamic/growing artificial cells. 14,15 In this Account, we will highlight new developments of synthetic and semisynthetic macromolecular coacervate materials in mimicking cellular systems. We start with briefly discussing some fundamental aspects of coacervate formation, including an overview of the synthetic macromolecules used for coacervate artificial cells to date.…”
Section: Introductionmentioning
confidence: 99%